Balancing conservation and community needs: challenges, threats, and socioeconomic disparities in Kakamega Forest, Kenya - Osewe, Ibrahim; Coman, Claudiu; Talpă, Nicolae; Osewe, Erick O.; Ndalilo, Leila; Kagombe, Joram K.; Abrudan, Ioan Vasile; Popa, Bogdan (Frontiers Media SA, 2025)
Introduction This research explores the perceptions of local forest communities in Kakamega Forest Ecosystem (KFE) regarding forest conditions, associated threats, Ecosystem services (ES) provision, and associated challenges with a focus on socioeconomic differences (wealth categories). Effective forest management is imperative for sustaining ES, but in KFE, threats to the forest and challenges local communities face hinder their provision. Methods Mixed method research was utilized, with qualitative data collected through Key Informant Interviews (KII), Focus Group Discussions (FGD), and quantitative data gathered through household surveys. Results and discussion The findings indicated that wealthier households exhibited a positive correlation with perceptions of unchanged ES provision, while poorer households showed a positive correlation with perceptions of decreased ES provision. Local communities generally perceived an improvement in forest conditions across the wealth categories. However, unexpectedly, poorer households associated highly improved forest conditions with decreased ES provision, indicating challenges related to access to ES. In contrast, middle and rich households expressed a positive correlation with perceptions of severely degraded forest conditions. Illegal logging emerged as the most significant threat to KFE, regardless of wealth category, followed by a lack of awareness of conservation efforts, with significant differences in perception across wealth categories. Surprisingly, animal grazing was perceived as a relatively low threat, with significant differences between wealth groups highlighting the importance of land ownership. The allocation of harvesting rights to non-local community members was identified as the most significant challenge faced by the local community, irrespective of wealth. Additionally, the prohibition of maize planting in the Plantation Establishment for Livelihood Improvement Scheme (PELIS) emerged as another major challenge across wealth categories, underscoring the importance of PELIS lands for cultivating staple foods. The electric fence was also perceived as a challenge by the local community, with significant differences between rich and poor households, reflecting the greater reliance of poorer households on provisioning ES. Conclusion This research provides valuable policy insights on community outreach, agricultural crops, harvesting, and the monitoring of participatory forest management (PFM). The findings support more inclusive, sustainable, and equitable management of KFE and other forest ecosystems to enhance the wellbeing and livelihoods of local forest communities.